Anxiety characteristics in individuals with Williams syndrome. Issue 4 (9th February 2021) - Royston, Rachel; Oliver, Chris; Howlin, Patricia; Waite, Jane
Abstract: Background: Williams syndrome anxiety research predominantly focuses on disorder prevalence and symptomatology, categorised using standardised mental health classifications. However, the use of these assessments may not fully capture the phenotypic features of anxiety in Williams syndrome. In this study, we examined characteristics of anxiety using a formulation framework. Method: A semi‐structured interview was conducted with thirteen parents of individuals with Williams syndrome (median age: 19, age range: 12–45, 8 females). Results: Various anxiety triggers were reported, including anxiety triggered by phobias, uncertainty and negative emotions in others. The range of described behaviours was diverse with both avoidant and active coping strategies for anxiety management reported. Conclusions: Many of the characteristics described were consistent with findings in the intellectual disability and typically developing literature, although novel information was identified. The study demonstrates the utility of a formulation framework to explore anxiety characteristics in atypical populations and has outlined new avenues for research.